Talent in female gymnastics: a survival analysis based upon performance characteristics - Pion, J.; Lenoir, M.; Vandorpe, B.; Segers, V. (International Journal of Sports Medicine, 2015)
This study investigated the link between the anthropometric, physical and motor characteristics assessed during talent identification and dropout in young female gymnasts. 3 cohorts of female gymnasts (n=243; 6-9 years) completed a test battery for talent identification. Performance-levels were monitored over 5 years of competition. Kaplan-Meier and Cox Proportional Hazards analyses were conducted to determine the survival rate and the characteristics that influence dropout respectively. Kaplan-Meier analysis indicated that only 18% of the female gymnasts that passed the baseline talent identification test survived at the highest competition level 5 years later. The Cox Proportional Hazards Model indicated that gymnasts with a score in the best quartile for a specific characteristic significantly increased chances of survival by 45-129%. These characteristics being: basic motor skills (129%), shoulder strength (96%), leg strength (53%) and 3 gross motor coordination items (45-73%). These results suggest that tests batteries commonly used for talent identification in young female gymnasts may also provide valuable insights into future dropout. Therefore, multidimensional test batteries deserve a prominent place in the selection process. The individual test results should encourage trainers to invest in an early development of basic physical and motor characteristics to prevent attrition